Adaptations to the One-Child Policy: Chinese Young Adults’ Attitudes Toward Elder Care and Living Arrangement After Marriage - Chen, Xiaochen; Zhuoga, Cuo; Deng, Ziqian (Frontiers in Psychology, 2021)
After four decades of China’s family planning policy, the shrinking family size and increasing life expectancy pose special challenges for the one-child generation in terms of providing care for aging parents. The current study explored young adults’ responses to such pressure by examining their concerns about elder care, attitudes toward nursing homes, and living arrangement after marriage in a sample of 473 Chinese working young adults from six cities in China (46.9% males, Mage = 25.1 years, 47.8% only children). Results showed that although most of the young adults reported to have thought about the issue of parents’ elder care, the majority did not worry a lot about it. Only children expressed similar levels of worrying as those with siblings did. However, educational level, rather than sibling status, was systematically related to concerns about parents’ elder care and attitudes toward nursing homes. People with higher education tended to worry less about elder care, and were less likely to consider placing parents in nursing homes as a violation of filial piety. Analyses of the married sub-sample (n = 140) revealed that only children were more likely to co-reside with parents after marriage than those with siblings. And the main reason for co-residence was that the younger generation needed their parents’ help for childcare, rather than to better take care of their parents. Implications for parents’ elder care among Chinese only children were discussed.